Financial Distress Dikaji Berdasarkan Rasio Keuangan pada Perusahaan Sektor Tekstil dan Garmen yang Terdaftar di BEI Tahun 2022-2023 - Nur Fadilla; Agung Wibowo; Janti Soegiastuti (Jurnal Ekonomi Manajemen Akuntansi, 2025)
Manufacturing companies in the textile and garment sector play an important role in the national economy, contributing to global development every year, creating jobs and encouraging domestic and foreign investment. However, the influence of globalization triggered by the influence of internal and external parties can cause many companies to experience financial difficulties. So researchers are interested in conducting research using secondary data in the form of annual financial reports. This study aims to evaluate financial ratios related to the company's financial distress conditions and identify factors causing financial difficulties in companies in the textile and garment sector listed on the Indonesia Stock Exchange in 2022-2023. This study uses the Springate (S-Score) method and logistic regression analysis with the results of the analysis showing that liquidity has a significant negative effect on financial distress, leverage has a positive insignificant effect on financial distress, and profitability has a significant negative effect on financial distress, and activity has a positive insignificant effect on financial distress.